Determinan Kebijakan Dividen di Bursa Efek Indonesia - Serly, Serly; Yukie, Haris (E-Jurnal Akuntansi; Vol 32 No 11 (2022)DO - 10.24843/EJA.2022.v32.i11.p12, 2022)
The study aims to analyze the determinants of dividend policy in companies listed on the Indonesia Stock Exchange (IDX) in the period 2016 to 2021. The variables studied in this study include liquidity, profitability proxied by Return on Equity (ROE) and Return on Assets (ROA). , solvency, company size, free cash flow, asset tangibility, investment opportunities, life cycle, and company risk. The research sample totaled 1,620 data obtained from 270 companies during the 2016-2021 period which were selected through purposive sampling. The total number of outlier data is 179 data so that the final data studied is 1,441 data. Panel regression analysis was applied as a test method in this study. The results of the study prove that liquidity, ROA, and free cash flow significantly influence dividend policy, while the other variables studied are not factors that influence dividend policy in companies listed on the IDX. Keywords: Dividend Policy; Dividend; Firm Characteristics; Financial Ratios